Risk Assessment of Cyclophosphamide and Mycophenolate Mofetil after Induction Treatment of Lupus Nephritis: A Single Center Quasi-Experimental Study - Kamal, Rosanna Bintey (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2023)
Background: The comparative safety of immunosuppressive drugs such as cyclophosphamide and mycophenolate mofetil for patients with lupus nephritis remains controversial. The study aimed to investigate the specific side effects of cyclophosphamide and mycophenolate mofetil in lupus nephritis patient after induction treatment. Materials and methods: It was a quasi-experimental study performed in the Department of Nephrology of Chittagong Medical College Hospital. A total of 100 patients of lupus nephritis who fulfilled the designated criteria were enrolled in this study by non-probability voluntary sampling method. The treatment was given on patient’s choice. After screening and treatment initiation, patients were assessed at 12 and 24 weeks. All the data were compiled in a structured case record form. Results: In the present study 48 patients (53.3%) in mycophenolate mofetil group and 42 patients (46.7%) in intravenous cyclophosphamide group completed 24 weeks of induction treatment of lupus nephritis. Infections were common in both treatment groups but significantly higher with intravenous cyclophosphamide group ((33.3% vs. 8.3%). Upper gastrointestinal syndrome occurred with 20(41%) patients in mycophenolate mofetil group and 7(16.7%) patients in intravenous cyclophosphamide group (RR=5.8333). Regarding other adverse effect, 10 patients of intravenous cyclophosphamide and two patients of mycophenolate mofetil group had amenorrhea (23.8% vs.4.2%). Alopecia (11.9%) was seen only by intravenous cyclophosphamide group ((RR=0.0798). Conclusion: Induction therapy with Mycophenolate mofetil was superior to intravenous cyclophosphamide in lupus nephritis in this study. Mycophenolate mofetil appeared to be better tolerated than cyclophosphamide. Chatt Maa Shi Hosp Med Coll J; Vol.22 (1); January 2023; Page 28-32